Medicinal effects of Ephedra foeminea aqueous extracts: Metabolomic characterization, biological evaluation, and molecular docking - Giulia Bennici; Inas Al Younis; Abeer Sharfalddin; Mutaz Akkawi; Fuad Al-Rimawi; Khaled Sawalha; Abdul-Hamid Emwas; Mariusz Jaremko (PLoS ONE, 2025)
Ephedra foeminea Forssk. is a medicinal plant traditionally used across various cultures and recognized for its historical significance in herbal medicine. It has been used as an herbal infusion to treat multiple respiratory diseases, headaches, and nasal congestion, as well as to prevent and manage breast cancer. In order to evaluate the validity of this ancestral knowledge, we aimed to investigate hot aqueous extracts of E. foeminea branches and fruits firstly by using untargeted metabolomic analysis, characterizing the chemical profiles of hot aqueous extracts from E. foeminea branches and fruits through the use of nuclear magnetic resonance, gas chromatography–mass spectrometry, and liquid chromatography–mass spectrometry. Subsequently, two in vitro studies were conducted to assess the anticancer and antioxidant potentials of the extracts. Antioxidant activity was evaluated using a 2,2-diphenyl-1-picrylhydrazyl assay and a total phenolic content assay. Anticancer activity was evaluated by assessing cytotoxicity using the MTT assay on MCF-7 (human breast cancer) and HeLa (cervical cancer) cell lines. Additionally, molecular docking was performed to explore the interactions between compounds identified in E. foeminea and selected cancer-related proteins, as well as the main protease of SARS-CoV-2. The results revealed that the branch extract exhibited superior antioxidant activity compared to the fruit extract, which was associated with a higher phenolic content in the branch extract (49.5 ± 0.7 mg GAE/g). The fruit extract exhibited greater cytotoxicity against MCF-7 cells, suggesting potential anticancer activity. Molecular docking analysis identified henryoside, guajavarin, and neohancoside as the most active compounds with anticancer and antiviral properties. These findings support the traditional use of E. foeminea Forssk. and highlight its potential as a source of bioactive compounds for further research into therapeutic applications.